Shock response in cage-like polynitrocubane high-energy-density materials: Competition between strain energy and structural symmetry - Qing-guan Song; Li Meng; Sheng-li Jiang; Lei Zhang; Ze-yao Mo (Energetic Materials Frontiers, 2025)
The cage-like structures provide a unique combination of strain energy for enhanced energy storage and hyperstatic constraints to stabilize the system, positioning them as promising pioneers in advancing high-energy-density materials (HEDMs). However, the shock response of cage-like HEDMs is highly complex and exhibits significant variability, posing a grand challenge in the underlying mechanisms. This study reveals that the shock response of cage-like HEDMs is regulated by the interplay between strain energy and structural symmetry, and introduces a physical model to quantitatively describe how they determine shock stability. The investigated systems include a comprehensive series of cage-like polynitrocubane HEDMs, with each carbon atom in the backbone progressively functionalized with nitro groups. Ab initio molecular dynamics (AIMD) simulations were employed to simulate dynamic and kinetic responses at shock velocities ranging from 8 km·s−1 to 11 km·s−1, with validation provided by consistent Hugoniot curves that align with reported experimental data. Nitro groups at the carbon-based cage structure, recognized as explosion functional groups, were found to substantially increase the system's strain energy. However, an increasing number of nitro groups also intensified electrostatic repulsion among oxygen lone pairs, which weakens structural integrity and renders the material more susceptible to disassembly under shock conditions. Conversely, structural symmetry—including both the cage-like molecular conformation and spatial packing within the crystal lattice—was found to mitigate these destabilizing effects, effectively balancing the trade-off between energy storage and structural stability. Based on these findings, we propose a physical model that captures the essential factors driving shock initiation in cage-like polynitrocubane HEDMs, offering new insights to inform the design and application of novel advanced HEDMs.